Farmers’ Distress in Uttar Pradesh, India – Lesson from a Research Study - Narain, Sarju; Singh, A. K.; Gupta, Shobhana (International Journal of Bio-resource and Stress Management, 2015)
Indian Economy is primarily based on Agriculture, where more than 85% farmers belong to small and marginal categories that face agrarian distress due to several causes. With this background, a research study was conducted in Bundelkhand region of Uttar Pradesh, Indiato assess the factors responsible for distress among farmers as well as to find out the agrarian distress vulnerability and to suggest extension strategy to prevent agrarian distress proneness levels. The study revealed that 65.72% farmers of this region were moderately to highly vulnerable to stress. Non profitable price of farm produces, poor return from farming, and monsoon/ weather related uncertainties, high cost of cultivation, and lack of irrigation facilities, etc. are mainly responsible for farmers’ distress. Only 5.14% farmers were found resistant to stress. Stress vulnerability related perception showed that distress regarding poor return from farming due to poor productivity was seen in nearly 59.71% farmers, while 58% farmers were in distress due to low market price of agricultural produces. Study revealed that 54.58 % farmers were vulnerable due to uncertainty of monsoon. Therefore, increasing the productivity level of farming through various strategies is urgently needed to assure profitable price of farm produce, develop weather forecasting system, crop insurance, etc. and launch a social awareness programme for stress management.